Nrac, a novel nutritionally-regulated adipose and cardiac-enriched gene. - Ren Zhang (Public Library of Science (PLoS), 2012)
Obesity increases the risk of multiple diseases, such as type 2 diabetes and coronary heart diseases, and therefore the current obesity epidemic poses a major public health issue. Therapeutic approaches are urgently needed to treat obesity as well as its complications. Plasma-membrane proteins with restricted tissue distributions are attractive drug targets, because of their accessibility to various drug delivery mechanisms and potentially alleviated side effects. To identify genes involved in metabolism, we performed RNA-Seq on fat in mice treated with a high-fat diet or fasting. Here we show that the gene A530016L24Rik (human ortholog C14orf180), named Nrac, is a novel nutritionally-regulated adipose and cardiac-enriched gene. Nrac is expressed specifically and abundantly in fat and the heart. Both fasting and obesity reduced Nrac expression in white adipose tissue, and fasting reduced its expression in brown fat. Nrac is localized to the plasma membrane, and highly induced during adipocyte differentiation. Nrac is therefore a novel adipocyte marker and has potential functions in metabolism.